Analisis Collaborative Governance Pemungutan Retribusi Pasar di Kecamatan Cimanggis Dalam Rangka Meningkatkan Pendapatan Daerah Kota Depok Tahun 2022 (Studi Kasus di Pasar Cisalak) - Tirtaningrum, Catur Wahyu; Selvi, Selvi (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
The background of this research was the receipt of the retribution fee from the Cisalak Market in Depok City, which had not reached the specified target in the last 3 years and the discovery of increasing unoccupied stalls and stands. This research aimed to identify the form of Collaborative Governance that had been applied in the collection of market retribution fees at Cisalak Market. This research used descriptive qualitative research method. Data collection used interview, observation, and documentation techniques. The research results show that the Collaborative Governance has been implemented well and appropriately, and has involved contributions from the Government and the community. However, the Collaborative Governance in the collection of market retribution fees has not been able to increase retribution revenue to the maximum level as the specified target. This is because many illegal traders sells their items outside the market building area causing the closure of market stalls and stands. In addition, there are still many traders who have not been educated regarding the implementation of e-retribution application which is expected to provide convenience and comfort in the retribution payment process. The government and the market management still make efforts by providing strict sanctions in the form of disciplinary order and fines for illegal traders. Socialization regarding e-retribution application continues to be improved to enable traders to immediately get benefits in the form of security and comfort from fulfilling their retribution obligations; transparency can also be achieved so that in the future, especially traders, can participate in monitoring the retribution collection process.